Effectiveness of Participatory Planning for Community Development: A Case Study on Ward No-6 in Pabna Municipality - Parvez, Mazed (Electronic Journal of Education, Social Economics and Technology, 2020)
In modern-day global, network participation is taken into consideration as the prerequisite of sustainable urban improvement. Its levels from just informing people approximately the plan or improvement projects utilizing the humans. However, public participation in neighborhood authorizes led applications is nonetheless confined in   Bangladesh. Increasingly, community participation is considered important in ensuring the sustainability of community utility services. In return, better access to all service facilities such as water supply, gas supply, transportation, health care, recreational area, electricity supply, etc. are important in the development of the living standard of the communities of an area. As the rate of community participation, this paper reconnoiters the extent of public participation in spatial planning performs in the Pabna municipality built totally on the citizen’s responses. Data were collected from community service facilities of ward no-06 in Pabna Municipality, Pabna District. Community Effect Index (CEI) and User Satisfaction Index (USI) were used to assess the performance of the community level utility services. The results indicate whether community-level utility services were effective or not. There is a general need to improve the quality and quantity of other services facilities like recreation facility, market facility, health facility, solid waste management system and transportation facility, and a need to improve authorized sections i.e. Municipality authority as well as NGOs to provide better services in this area.